Prevalence of coronary artery disease and its associated risk factors in Aljouf region of Saudi Arabia - Ali Sheikh, Md Sayed (Bangladesh Journal of Medical Science, 2022)
Objective:Toevaluate the prevalence of coronary artery disease (CAD) with its associated risk factors among Saudi population in Aljouf, Sakaka, Saudi Arabia. Methods: This is a retrospective hospital based study conducted at King Abdul Aziz specialized hospital Sakaka Aljouf, Saudi Arabia by selecting participants with diagnosed CAD by coronary angiogram, the meanage 55.1 ± 10.8 yrs ( range 35-75-years)over a period ofJanuary 2019to December 2019. Demographic characteristics included age, sex,diabetes, hypertension, smoking and family history of CAD. Laboratory data included such as total cholesterol, triglyceride, LDL and HDL levels. Collected data were analyzed by using SPSS 20.00software. Results: One hundred two participants, out of eight hundred fifty five were diagnosed CADwhich included 64.7% stable angina and 35.2% unstable angina. The total prevalence of CAD obtained from this study was11.9% among male and female was7.89% and 4.621% respectively (P<0.0001). Diabetes (85.7%) and dyslipidemia 94.2%weremost important risk factors in female compared to male 59.1% and 62.2% respectively, while hypertension 82% higher in male than female 51.4 % considers as a significant (p<0.001). Smoking considered as an individual risk factor of 94% for male coronary artery disease patients. Conclusion:The prevalence of CAD was higher in male 7.89 % than female 4.21% and its associated risk factors including hypertension and cigarette smoking. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 201-205